Screening a European Avena landrace collection using morphological and molecular markers for quality and resistance breeding - Katsiotis A.; Germeier C.U.; Koenig J.; Legget M.; Bondo L.; Frese L.; Bladenopoulos K.; Ottoson F.; Mavromatis A.; Veteläinen M.; Menexes G.; Drossou A. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The genetic diversity of about 1,000 Avena sativa and A. byzantina landrace accessions from European genebanks has been studied. Morphological and agronomic characters have been recorded under in diverse environments and controlled disease resistance screenings were performed for crown rust, stem rust and powdery mildew. Only few landraces were found to be immune or very resistant to the above mentioned pathogens. Protein content for all accessions ranged from 9.8 percent to 19 percent. A single AFLP primer pair provided enough polymorphic bands to discriminate more than 180 accessions.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)